2013
DOI: 10.3947/ic.2013.45.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Praziquantel Treatment in Trematode and Cestode Infections: An Update

Abstract: Status and emerging issues in the use of praziquantel for treatment of human trematode and cestode infections are briefly reviewed. Since praziquantel was first introduced as a broadspectrum anthelmintic in 1975, innumerable articles describing its successful use in the treatment of the majority of human-infecting trematodes and cestodes have been published. The target trematode and cestode diseases include schistosomiasis, clonorchiasis and opisthorchiasis, paragonimiasis, heterophyidiasis, echinostomiasis, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
129
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(143 citation statements)
references
References 69 publications
6
129
0
3
Order By: Relevance
“…Different studies showed failure of human treatment against fascioliosis with praziquantel (Farag et al, 1986;Farid et al, 1989;Chai, 2013). Such failure may be related to the resistant properties of the F. hepatica tegument.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies showed failure of human treatment against fascioliosis with praziquantel (Farag et al, 1986;Farid et al, 1989;Chai, 2013). Such failure may be related to the resistant properties of the F. hepatica tegument.…”
Section: Discussionmentioning
confidence: 99%
“…Low drug concentration or, in other words, sublethal PZQ concentration is a hypothesized cause of schistosomal resistance to drug treatment (9). Another considerable concern is that complete dependence on PZQ as the sole drug for treating schistosomiasis may favor the prospects of emerging resistance to the drug (10).…”
mentioning
confidence: 99%
“…PZQ is a broad-spectrum, highly efficacious, and safe anthelmintic against trematode and cestode infections in humans and animals, respectively (Chai, 2013). Emerging problems include the appearance of PZQ-resistant strains or isolates in S. mansoni and S. japonicum in the laboratory (Liang et al, 2002(Liang et al, , 2010 or in the field (Wang et al, 2012).…”
Section: Discussionmentioning
confidence: 99%